Enhancing self‐care strategies in heart failure through patient‐reported outcome measures. Issue 8 (7th August 2018) - Segan, Louise; Nanayakkara, Shane; Mak, Vivian; Kaye, David
Abstract: Heart failure (HF) is a major cause of morbidity and mortality, requiring collaborative patient‐centred care. Patient engagement is fundamental to long‐term management; patient‐reported outcome measures are an increasingly recognised method of assessing medical interventions. A qualitative study of 31 patients with HF found they were twice as likely to use their own management strategies including electronic platforms rather than existing resources. Barriers to self‐care included patient education, timely recognition of signs and symptoms of HF with an appropriate escalation plan, non‐adherence and polypharmacy.